Ukraine and the Council of Europe common activity in implementation of key principles of participatory democracy - Mykhaliuk Nazar Yuriyovych (Studia Humanitatis, 2015)
The article analyses the main forms of mutual cooperation of Ukraine and the Council of Europe in order to implement basic principles of participatory democracy, to conform the legislation of Ukraine to standards of the European Union. The article examines the main legal documents, phases, and the main areas of cooperation between Ukraine and the Council of Europe. The author also assesses the processes of implementation of key principles of participatory democracy in Ukraine.